Ewolucyjny charakter zmian warunków pracy w przedsiębiorstwach a ich kształtowanie w niepublicznych zakładach opieki zdrowotnej (NZOZ) - Cierniak-Emerych, Anna; Napora, Piotr (The evolutionary character of changes of working conditions in enterprises and their shaping in non-public health care centres (NZOZ), 2006)
The paper presents an attempt to show circumstances and directions of changes of working conditions in organizations functioning in Poland. Considering these changes in connection with transformations in Polish economy and in consequence in enterprises, the attention was Focus on their evolutionary character. It becomes a background for imaging the problem of shaping working conditions in Non-Public Health Care Centres (NZOZ).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 210-216